Oral hygiene in 12-year-old disabled children in Flanders, Belgium, related to manual dexterity - Hausen H, Ka¨rkka¨inen S, Seppa¨ L (Blackwell Synergy, 2000)
As part of a larger epidemiological survey of a stratified sample of 12- year-old handicapped children in Flanders, Belgium, the present study describes gingival health, gingival hypertrophy, oral cleanliness and the presence of calculus. Statistical analysis was performed with motor skills, brushing help, the use of chemical agents, the use of anti-epilectic drugs, the knowledge of parents and educators (or caregivers) and their opinion of the oral hygiene of their children/ pupils as response variables.